How does inflammation contribute to pulmonary hypertension?. Issue 1 (25th January 2018) - Kumar, Rahul; Graham, Brian
Pathogenic drivers of the pulmonary vascular disease that results in pulmonary arterial hypertension (PAH) are currently unclear, but there are many reasons to suspect that inflammation is a major contributor. Clinically, PAH is a complication of multiple autoimmune diseases including scleroderma and systemic lupus erythematosus, suggesting dysregulated immunity can trigger the vascular disease [1–3]. PAH can also complicate several infectious diseases, including HIV and schistosomiasis, suggesting there could be off-target effects of immune upregulation which inadvertently damage the pulmonary vasculature. Patients with these pro-inflammatory aetiologies often have systemic vascular diseases, including digital ischaemia in scleroderma and portal hypertension in schistosomiasis [4, 5], suggesting the same inflammatory stimuli can lead to diverse vascular pathologies. Blocking inflammation could be a curative approach in pulmonary vascular diseases http://ow.ly/dW5M30hB6aj